“Using the "glass ceiling" indicator to measure the extent of its existence in the Malaysian corporate sector” / Nurul Azwa Mohamed Khadri, Geetha Subramaniam and Rohayu Abdul Razak - Mohamed Khadri, Nurul Azwa; Subramaniam, Geetha; Abdul Razak, Rohayu (Research Innovation Business Unit, 2014)
Malaysia has undergone a transformation over the past few decades as they move from being a primarily agrarian society to a more modern industrial society. These economic changes have an important implication on demographic and labour issues which noted an increase in demand for a highly skilled workforce. The growth of Malaysian economy has created many new job opportunities for Malaysians including women. As a result, women in Malaysia have entered the workforce in increasing numbers. Overall, female participation in the labour force has accounted for 49.4 % of 4,546,300 as reported in the 2012 Labour Force Survey Report as compared to only 24.5 % in 1957. Although the number of women participations in labour force shows an increasing number, there is still a lack of women involvement in top management positions. Malaysia is the third lowest to have women on the board of companies as Chief Executive Officer, Chief Financial Officer, Executive and Non-executive Directors, which is only 13 % as reported in 2013 by Grant Thornton International Business Report. A recent survey shows that an increasing number of women in high level positions can improve company’s financial performance and at a same time will expand the country’s economy. The best term that can be used to represent the barriers that hindered women’s career advancement is “glass ceiling”. “Glass ceiling” symbolizes a variety a barriers faced by women as they seek to improve their employment status in the organization. The concept of “glass ceiling” refers to challenges faced by women who attempt to retain senior positions as well as higher salary levels. The implications of “glass ceiling” range of micro level issues such as dissatisfaction and exit from the labor force to macro issues such as brain drain and migration. This study aims to examine whether the “glass ceiling” phenomena exist in the corporate sector in Malaysia. Women working in the corporate sector are given a questionnaire with 10 items. By using this measurement, we will be able to assess whether these working women perceive that they are confronted with a “glass ceiling”. This indicator will show us that if women perceive there is a “glass ceiling” in their organization highly likely that these women will exit the labour force before retirement age. Hence, the organizations might need to take some steps to resolve the issues women workers face. Using economic theory of human capital investment and labour market discrimination, the measurement will be able to gauge to what extent “glass ceiling” may be an issue to women’s progress in the career path and hence their retention in labour market. This is crucial as women constitute 50% of Malaysia’s labor force, which needs to be tapped efficiently in order for the country to achieve its vision to attain an industrialized nation by 2020.